Uncle Wiggily's Airship - Garis, Howard Roger, 1873-1962; Wisa, Louis, 1873-1953 (Salt Lake City, UT : Project Gutenberg, 2023)
"Uncle Wiggily's Airship: Bedtime Stories" by Howard Roger Garis is a collection of children's stories written in the early 20th century. The book follows the adventures of Uncle Wiggily Longears, an endearing old gentleman rabbit who embarks on whimsical journeys in his unique airship, which is fashioned from a clothes basket, toy balloons, and an electric fan. The stories are characterized by their playful language, humor, and the underlying theme of kindness and problem-solving. The opening of this charming collection introduces readers to Uncle Wiggily as he dreams of flying in his airship. After a humorous mishap involving Mother Goose accidentally dropping pins that burst his balloons, he quickly devises a method to rebuild his airship, demonstrating his resourcefulness and determination. Accompanied by Nurse Jane, a muskrat lady, Uncle Wiggily$1 (Bs escapades lead him to encounter a variety of characters, such as the monkey shopkeeper and Dr. Possum, all of whom contribute to the story's lighthearted and adventurous spirit. This introduction sets the tone for a series of delightful tales that are sure to entertain young readers at bedtime. (This is an automatically generated summary.)s
Release date is 2023-03-15
Bob Taylor, David Edwards and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Animals -- Juvenile fiction; Rabbits -- Juvenile fiction; Uncle Wiggily (Fictitious character) -- Juvenile fiction; Balloons -- Juvenile fiction